Integrasi Nilai Nilai Pendidikan Multikultural Melalui Kegiatan Keputrian di SMPN 7 Mataram - Zaki, Muhamad; Risma, Napassanaye; Alivia, Neta; Batrisyia Azizah Sudiarta, Najwa; Arya Ramadhana, Muhammad; Sawaludin, Sawaludin (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
This study aims to analyze the integration of multicultural education values through the girls’ activity program at SMPN 7 Mataram and its impact on students’ attitudes. A qualitative approach was employed, collecting data through semi-structured interviews, non-participatory observation, and documentation involving the program instructors and junior high school students. Findings indicate that the program not only develops religious aspects but also instills values of tolerance, togetherness, respect, and social care through contextual lectures, discussions, and case studies. These values foster students’ openness, empathy, social responsibility, and understanding of differences, while enhancing solidarity and inclusive social interaction. The study highlights that the girls’ program serves as an effective medium for multicultural education, providing a model for character development in schools with diverse student populations, reducing social conflict potential, and strengthening peer cohesion.